Penyuluhan Tentang BBLR Dan Wasting Pada Ibu Hamil Dan Ibu Balita Di Bengkong Sadai, Kota Batam - Aprilya Roza Werdani; Justiyulfah Syah; Putri Ranatul Agustri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
In 2018, Basic Health Research (Riskesdas) data showed that the prevalence of wasting in children under five in Indonesia was 10.2%, while in the age group under two years (baduta) it was higher, namely 11.7%. Nutrition Status Monitoring Data for 2017 also shows that the prevalence of wasting in under-fives is higher, which is 12.8% when compared to the toddler group, which is 9.5% (Ministry of Health RI, 2018). Based on the WHO classification, wasting in the underdog group in Indonesia is categorized as a serious public health problem, with a prevalence in the range of 10-14%. Malnutrition that occurs in 1,000 HPK, besides being at risk of inhibiting physical growth (failure to thrive) and being susceptible to disease (metabolic disorders: DM. Hypertension, obesity), also inhibits cognitive development (motor cognitive impairment) which will affect the level of intelligence and productivity of children in the future.